"[T]he rising silhouette of the city" : une poétique des choses urbaines dans "Coming, Aphrodite !" et "The Diamond Mine" de Willa Cather - Céline Manresa (Anglophonia)
In most of her novels, Willa Cather situates her fiction within the vast, untrodden expanses of the American West. However, as Cather temporarily decided to turn away from the natural landscapes of the West in order to approach the city, she had to find a new mode of writing. Indeed, if the novel’s format fits the ever-stretching horizontality of the wilderness, the condensed space of the short story seems to be harmoniously adjusted to the architectured yet protean texture of the city. By focusing on two short stories devoted to the representation of New York at the turn of the twentieth century—"Coming, Aphrodite!" and "The Diamond Mine"—, this analysis aims at showing that in her short stories in particular, Cather invents a genuine poetics of urban concreteness. She establishes a subtle compromise between realist and modernist approaches. Indeed, avoiding any panoramic view of the setting, Cather succeeds in conveying an elusive and fragmentary evocation of New York City. In order to create an intimate urban cartography, Cather emphasizes a selection of topographic and architectural landmarks emerging in the blur of the city. Now, if material things simultaneously delineate and fashion the outlines of the city, they also contribute to the modelling of the protagonists’ bodies. Elaborating an analogy between the partially veiled and yet carnal silhouettes of the heroines and the hazy yet concrete contours of the city, Cather’s writing moves from a pictorial to a sculptural dimension. Sensitive to the ever-renewed colours, lights, sounds and shapes of the city, Willa Cather’s literary language is permeated by the intensity of the urban experience, which ultimately paves the way for a poetic encounter between the text and the tangible world of the city.